-5(7x-5)-1=6(1-6x)+7

Simple and best practice solution for -5(7x-5)-1=6(1-6x)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(7x-5)-1=6(1-6x)+7 equation:



-5(7x-5)-1=6(1-6x)+7
We move all terms to the left:
-5(7x-5)-1-(6(1-6x)+7)=0
We add all the numbers together, and all the variables
-5(7x-5)-(6(-6x+1)+7)-1=0
We multiply parentheses
-35x-(6(-6x+1)+7)+25-1=0
We calculate terms in parentheses: -(6(-6x+1)+7), so:
6(-6x+1)+7
We multiply parentheses
-36x+6+7
We add all the numbers together, and all the variables
-36x+13
Back to the equation:
-(-36x+13)
We add all the numbers together, and all the variables
-35x-(-36x+13)+24=0
We get rid of parentheses
-35x+36x-13+24=0
We add all the numbers together, and all the variables
x+11=0
We move all terms containing x to the left, all other terms to the right
x=-11

See similar equations:

| 3x+15=2(x+15 | | 15=4w- | | 7-3x+6x+1=4(7-x)-2(1-8x) | | 10k-73=981 | | 2x+5x=9x−8 | | 4(x+2)=8(1-5x) | | -3+3(3+x)=-x+6(1+8x) | | 3^x+7=18^x | | 7(3n+6)-8(1+5n)=15 | | 9m²+0,27m=0 | | 7(3n+6-8(1+5n)=15 | | 5-4t=3 | | 4(6+4n)-7(8n-2)=-42 | | -35=-4(6n+8)-3(n-8 | | 1/4x+1/5=-6 | | 50=8(m-7)-7(-8-6m) | | 5p+6(-6+p)=-91 | | 7b+6(b+6)=114 | | N-380x7+1020=1860 | | 7(-7r-8)=448 | | 0=8n+3n | | x/3+6=22 | | -6x+3+7x=10 | | -7=r-7-r | | 50x210-N=3700 | | y=0.50(1.06)^80 | | 35=8x+8 | | N-245x5=175 | | a2=24 | | 2x=5x-9x+8 | | 10-y÷2=2 | | 6^x+3=3^x |

Equations solver categories